Quilombo Mata Cavalo : terra, conflito e os caminhos da identidade negra - Barcelos, Silvânio Paulo de (2011)
The specifically black identity in the remnants Comunidade de remanescentes do Quilombo Mata Cavalo, located in the town of Livramento, in Mato Grosso, are anchored conceptually welldefined two pillars: “land and the memory” of Sesmaria Boa Vida slaves, his ancestors. The lands that were donated by D. Anna da Silva Tavares liners to their slaves and captives in 1883 were responsible for their own source of Quilombo, creating a way of live based on relations of reciprocity and communal work, reminiscent of the fertile imagination and the legacy of slavery widespread black people in the diaspora. Why leave to chance and the fortune as owner of the lands they knew well, it was up to than the task of the expanding the higher ideal of freedom reterritorialized that space as a place for black, designed from the exchanged of memories and collectives experiences. Settler in that area to more then one hundred and twenty years, the descendant of slaves to resist, even today, to pressure from farmers in the region by the dispute over its ownership. The question maroon, arising from the Constitution of 1988 provides legal access routes for new ways of fighting for they lands, while contributing to the emergence of internal dissent in the Mata Cavalo. This alternative is equivalent, for those who remained in those lands facing all sorts of violence and the conflict, denial of they own history. Paradoxically, those remaining directly involved in the struggle for lands as protagonists of social weft singular, also appropriated the concept of “maroon” seeking a favorable outcome to the possible legal proceedings underway in the Federal Court. Thus in the XXI century the members of the community traditional fight for the preservation of a memory African-referenced while they dream to win recognition of their primordial, an area of black in a society marked by diffuse interest and the stigma of globalization.